Teacher Professionalism and Commitment to the Learning Quality of Class X Middle School Students in Lempuing District - Ahmad Fauzi; Edi Harapan; Mahasir Mahasir (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This study aims to determine the effect of teacher professionalism and teacher work commitment on the quality of teaching of Class X students in Middle School in Lempuing District. To achieve these objectives, using quantitative research methods. This research was conducted by SMA/MA in Lempuing District, Ogan Komering Ilir Regency, with a sample of 174 teachers from 8 SMA/MA selected by purposive sampling technique and used as the study population. Data collection techniques are systematic observation, literature study, questionnaires, and documentation. The operational definitions of the variables that will be presented are the operational definitions of the variables of professionalism (X 1 ), teacher work commitment (X 2 ) and the quality of learning of class X students of middle school in Lempuing sub-district ( Y). Based on the research that has been done, the results show that (1) there is a positive influence between teacher professionalism on the learning quality of class X Middle School in Lempuing sub-district, (2) there is a positive influence between teacher commitment to the quality of learning for class X Middle School in Lempuing sub-district, and (3) there is a positive influence between teacher professionalism and teacher commitment to the quality of learning for class X Middle School in the Lempuing sub-district.